(untitled) (Bangladesh Journal of Microbiology, 2019)
A pot experiment was carried out in the nethouse of Soil Science Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during 2014-2015 through 2015-2016. The design of the experiment was factorial randomized completely block design with 4 replications. The objectives of the study were to evaluate the potential of Arbuscular mycorrhization (AM) on the germination, nodulation and sporulation of lentil treated with different concentration of NaCl. Five NaCl treatments (0, 1, 2, 3 and 4%) possessed NaCl level as the first factor that were treated with soils before sowing of lentil seeds pivotal pulse crop in Bangladesh. The second factor consists of mycorrhizal and nonmycorrhizal treatments. Mycorrhizal plants showed better performance in terms of germination (%), nodule number, nodule weight, spore population/100 g soil and root colonization (%) than non-mycorrhizal plants. With increasing NaCl concentration, germination (%), nodule number, nodule weight, spore population/100 g soil and root colonization (%) in the rhizosphere soil, decreased significantly (p<0.01). The highest germination (96.25% in 2014-2015 and 92.50% in 2015-2016), nodule number plant-1 (28.67 in 2014-2015 and 24.34 in 2015-2016), and root colonization (30% in 2014-2015 and 43.34% in 2015-2016) was found in 0% NaCl + AM treatment. The lowest germination%, nodule number plant-1 and root colonization% was found in 4% NaCl treatment. Mycorrhizal inoculation increased germination on an average by 9.68% during 2014-2015 and 11.07% during 2015-2016, and increased root colonization on an average by 40.47% during 2014-2015 and 25.14% during 2015-2016 over non-mycorrhizal inoculation. The study clearly indicates that mycorrhizal inoculation could reduce the harmful effects of NaCl toxicity to the host plants, thus increase plant survival allowing the plants growth under extreme condition. Increased overall absorption capacity, absorption surface area and longevity of absorbing roots elevated NaCl concentration in soils resulting detoxify the environment for plant growth. Bangladesh J Microbiol, Volume 34 Number 2 December 2017, pp 73-81